CD8 T cells promote heart failure progression in mice with preexisting left ventricular dysfunction - Wang, Dongzhi; Weng, Xinyu; Yue, Wenhui; Shang, Linlin; Wei, Yidong; Clemmer, John S.; Xu, Yawei; Chen, Yingjie (Frontiers in Immunology, 2024)
Even under the standard medical care, patients with left ventricular (LV) failure or heart failure (HF) often progress to pulmonary hypertension and right ventricular (RV) hypertrophy. We previously showed that inflammation and regulatory T cells (Tregs) modulate HF progression in mice with preexisting LV failure. The main objective of this study is to determine the role of CD8+ T cells in modulating LV failure and the consequent pulmonary inflammation and RV hypertrophy in mice with preexisting LV failure. Mice with LV failure produced by transverse aortic constriction (TAC) were randomized to depletion of cytotoxic CD8+ T cells, Tregs, or both using specific blocking antibodies. Cardiac function, lung inflammation, fibrosis, vascular remodeling, and right ventricular remodeling were determined. LV failure caused pulmonary inflammation, fibrosis, vascular remodeling, and RV hypertrophy. Depletion of CD8+ T cells significantly attenuated above changes in mice with preexisting LV failure. LV failure was associated with increased CD4+ and CD8+ T activation, and increased ratios of activated T cells to Tregs. Treg depletion exacerbated lung inflammation and HF progression, as well as lung CD4+ and CD8+ T cell infiltration and activation in HF mice. However, CD8+ T cells depletion rescue these mice from exacerbated lung inflammation and RV hypertrophy after Treg depletion. Our findings demonstrate an important role of CD8+ T cells in promoting pulmonary inflammation and RV hypertrophy in mice with preexisting LV failure. Depletion of CD8+ T cells also rescued HF mice from the exacerbated HF progression by Treg depletion.